MENINGKATKAN PEMAHAMAN SISWA MENGGUNAKAN PENDEKATAN JELAJAH ALAM SEKITAR (JAS) DENGAN METODE EKSPERIMEN PADA MATERI LIMBAH - Erwan Erwan; Achyani Achyani (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
Student understanding is how a student is able to maintain, differentiated, assumed, explains, and What has been received. Understanding rather than merely thinking activities, but did experience the mind (experience life). The things to do to achieve student understanding is by ways student actively exploring learn directly. Approach to natural roaming around alternative in learning biology. In this approach, student are required actively exploring, learning envirotment as a source of biology, will be able to increase student’s understanding. Conclusions of this study, learning opproach to natural roaming around with experimental methods can increase student’s understanding in SMA Muhammadiyah 2 Metro school year 2011/2012 of pre-PTK to the cycle 2 be 54% and suggestion that research can be used increase the student’s understanding.Kata Kunci: Jelajah Alam Sekitar, Aktivitas Belajar, Hasil Belajar